Medicinal plant in animal feed - Pavkov, Sava; Kostadinović, Ljiljana; Lević, Jovanka (Economics of Agriculture, 2010)
The medicinal plants and herbs have been used for many years in the treatment of various diseases in animals and human beings. Now-a-days, utilization of these medicinal plants is increasing. These are used in animal feed as the growth promoters. Due to prohibition of most of the antimicrobial growth promoters in animal feed because of their residual effects, plant extracts are becoming more popular. They act as antibacterial, antioxidant, anticarcinogenic, antifungal, analgesic, insecticidal, anticoccidial and growth promoters. These plant extracts compete with the synthetic drugs. Majority of medicinal plants do not have the residual effects. The paper gives a short overview of the most important potential of herbal medicinal materials that have an approved application in human medicine and which can be added to animal feed for use in different animal health disorders.